Effects of thermal processing on sorghum phenolics and their potential for human health foods - Peterson, Jaymi Marie (My University, 2024)
Recent literature highlights the health benefits of pigmented grains such as rice, corn, and sorghum which are rich in polyphenols. These compounds offer numerous health advantages including antioxidant activity, anti-cancer, anti-diabetic, anti-hypertensive, and anti-obesity effects. This potential makes pigmented grains valuable as natural food additives or bio colorants in foods. Chapter 1 introduces sorghum as a whole and covers topics in sorghum nutrition, sorghum phenolic classifications, reported health benefits, and both traditional food uses for sorghum as well as current sorghum phenolic applications in foods. Finally, a gap in knowledge is presented and subsequently examined in the following chapters The objective of this dissertation is to investigate the effect of processing on sorghum phenolics to determine their potential for future functional food applications. Chapter 2 of this dissertation explores the phenolic profiles and bioactivities of various pigmented and non-pigmented rice, corn, and sorghum varieties. Sorghum was significantly higher in total phenolic content (TPC) by 67% in comparison to corn and 76% in comparison to rice. Sorghum was also significantly higher in antioxidant activity (AA) by 50% in comparison to corn and 45% higher than rice. Using the vanillin-HCl analysis, only sorghum had detectable condensed tannin contents (CTC). After further investigation using normal phase high pressure liquid chromatography (NP-HPLC), Sorghum was higher in total proanthocyanidin (condensed tannin) content by 96% in comparison to corn and 84% in comparison to rice. Using reverse phase HPLC, the phenolic profile of grains was examined. Rice and corn samples contained unique cyanidin and anthocyanidin compound while sorghum contained unique 3-deoxyanthocyanidins. Chapter 3 of this dissertation evaluates the effect of high moisture heat treatments at different pH levels on sorghum starch digestibility, phenolic profile and bioactivity. Brown whole grain sorghum flour was cooked with various buffers (pH 3, 4, 5, 7, 8) for 0, 10, 30, 60, or 120 minutes and then freeze dried for analysis. The results indicated that cooking for 10 minutes significantly (p<0.05) increased digestible starch. A 10-minute cooking duration did not significantly alter TPC but reduced condensed tannin content. Although 3-deoxyanthocyanidins decreased, some flavonoids remained stable or increased after processing. Cooking sorghum for 10 minutes did not significantly reduce cancer cell inhibition in HCT116 cells, except for pH 8. Overall, a 10-minute cooking time increased starch digestibility without significantly compromising health benefits. This further supports sorghum's potential as a health food ingredient. Chapter 4 of this dissertation further evaluates the effect of various heat processing methods on sorghum phenolics to better understand the potential for sorghum as a health food ingredient. Toasting or dry heat methods increased phenolic content or had no negative affect on phenolic content while extrusion also increased phenolic content or did not affect phenolic content. The bioactivity of sorghum polyphenols was significantly decreased after heat processing regardless of processing method. More studies are needed to understand the specific effect of each heat processing method on sorghum phenolics to fully utilize this grain for function food formulations. Chapter 5 of this dissertation discusses the implications of these studies and the future studies to be undertaken to promote sorghum as a health food for human populations.
Keywords: Sorghum; Phenolics; Processing; Polyphenols; Bioactivity